CREATIVE INDUSTRIES AND THE INNOVATIVE URBAN MILIEU: THE CASE OF THE METROPOLITAN CITY OF ROME - Lelo, Keti (Piccola Impresa / Small Business, 2025)
Purpose. In large cities creative industries tend to geographically concentrate. The purpose of this paper is to empirically test the hypothesis that this geographic concentration derives from the benefits on the innovative urban milieu. Design/methodology/approach. A spatial regression model is estimated using as dependent variable the number of creative firms per census block in the Metropolitan city of Rome. Empirical results show that the estimated coefficient of the spatially lagged dependent variable is significantly positive, indicating that the number of creative firms in a census block is influenced by the number of creative firms in neighboring blocks. This enables to explore the conditions accounting for the concentration of creative industries. Practical and Social implications. This paper suggests that knowledge externalities influencing the creative firm’s spatial distribution can be interpreted, in an urban scale, in terms of local spatial spillovers, which take the form of spatial dependence. The empirical analysis revealed the existence of a spontaneous creative geography within the metropolitan city of Rome, which is important to further analyse and interpret, if we want to look at the creative clustering from a policy perspective. Creative clusters represent a good opportunity for local governments to catch up with innovation and entrepreneurship policies therefore they need evidence about the existence and the potential role of creative clusters, if they are to encouraging creative industrial growth in particular places. Originality of the study. The paper aims to fill the gap between the regional and the urban scale of analysis in empirical studies on creative industries.